The Personality Of Ayyas In Bumi Cinta Novel By Habiburrahman El-Shirazy - Sugianto, Nanang; Setianingsih, Tri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
This research aimed to find out the Personality of Ayyas in Bumi Cinta novel by Habiburrahman El Shirazy. The method applied in this research was qualitative method. The object of this research was the personality of Ayyas’ character in Bumi Cinta novel by Habiburrahman El Shirazy through psychology review. The technique used in collecting the data was library research. The process of data analysis was data reduction, data display and conclusion drawing. The result of this study was found out that the personality of Ayyas was more dominant influenced by the superego. Based on the result of the study, it could be concluded that the personality of Ayyas influenced by the superego seems when Ayyas defended himself in the sanctity and his faith in the midst of the storms of free life country, having a firm belief and faith to God, Ayyas remained confident and believe in the grace of God to His people. Although there were some people who did not acknowledge the existence of God, Ayyas was always cling to the obligations of religion, implementing everything that God approves, and stay away from all His prohibitions, and reluctant to commit  sin and sinners, willing to sacrifice for the sake of religion and give helping.